Fabrication of Hierarchical Multilayer Poly(Glycerol Sebacate urethane) Scaffolds Based on Ice-Templating - Samourides, Andreas; Anayiotos, Andreas; Kapnisis, Konstantinos; Xenou, Zacharoula; Hearnden, Vanessa; Chen, Biqiong (My University, 2021)
In this study, it was demonstrated that ice-templating via freeze drying with custom-made moulds, in combination with air brushing, allows for the fabrication of poly(glycerol sebacate urethane) (PGSU) scaffolds with hierarchical multilayer microstructures to replicate various native soft tissues. The PGSU scaffolds were either monolayered but exhibited an anisotropic microstructure, or bilayered and trilayered, with each layer showing different microstructures. By using freeze drying with custom-made moulds, the ice crystals of the solvent were grown unidirectionally, and after freeze-drying, the scaffolds had an anisotropic microstructure, mimicking tissues such as tendon and skeletal muscle. The anisotropic PGSU scaffolds were also examined for their tensile strength, and a range of mechanical properties were obtained by altering the reactants’ molar ratio and polymer concentration. This is of importance, since soft tissues exhibit different mechanical properties depending on their native location and functionality. By combining freeze drying with airbrushing, scaffolds were fabricated with a thin, non-porous layer on top of the porous layers to allow three-dimensional cell co-culture for tissues such as skin and oral mucosa. These results show that fabrication techniques can be combined to produce PGSU scaffolds with tailored hierarchical microstructures and mechanical properties for multiple tissue engineering applications.
Keywords: Poly(glycerol sebacate urethane); Tissue engineering; Multilayer scaffold; Anisotropic scaffold; Soft tissue